Orientation Algorithms of a Strap-down Inertial Navigation System Using Rodrig - Hamilton Parameters - Chuc, Nguyen Van; Tuan, Le Anh; Thang, Nguyen Phu (VNU Journal of Science: Mathematics - Physics; Vol 19 No 2, 2003)
Abstract